«Ազդարար»-ում տպագրված հայատառ պարսկերեն մի գրության մասին - Կիրակոսյան, Հասմիկ (Մատենադարան)
In the issue of “Azdarar” of the month Shbat, 1795, a decree of Muhammad Ali Khan Wallajah (the Nawab of Arcot in India) was published. The document was in Persian written in the Armenian script. The decipherment and translation of the document proved that Armenian intellectuals were among initiators of the establishment of Arabic-script printing houses in Madras and had a crucial role in the geographic spread of Arabic-script printing culture. Furthermore, the document mentions the founder of the first Armenian journal “Azdarar,” Father Harutyun Shmavonyan, known for his printing activities. In a colophon of one of his printed books, Father Harutyun stated that his pupil Khachik Tsatur Zaipean was skilled in printing Persian letters, which was an essential factor for the successful establishment of an Arabicscript printing house. Also, a Persian version of the document written in the Arabic script was attached to this issue of “Azdarar,” proving the lack of Arabic-script printing facilities and the necessity to print the Persian material in Armenian letters. Presumably, the Armenian community of India was familiar with the written version of Persian and knew the Arabic script as well, but the use of the Armenian script also had a symbolic, moral, and psychological significance for Armenians. В номере за месяц Шбат 1795 года в журнале “Аздарар” был опубликован документ на персидском языке, написанный армянскими буквами – указ наваба индийского княжества Аркот Мухаммада Али Хан Валладжаха. Транскрипция и перевод текста показывают, что армянские интеллектуалы были инициаторами создания типографии в Мадрасе для печатания арабописьмен- ных книг и газет. Зачинателем этого дела был основатель первого армянского журнала “Аздарар” Транскрипция Арутюн Шмавонян. Кроме того, в колофоне одной из книг, напечатанных им, он сообщает, что один из его учеников (Хачик Цатур Заипян) владел искусством создания типографских персидских букв, и это было залогом успеха в в деле основания им арабописьменной типографии. Персидский вариант вышеупомянутого документа, написанный арабским письмом, был приложен к номеру журнала, и это также свидетельствовало об отсутствии такой типографии. При этом представители армянской общины Индии владели устным и письменным вариантами персидского, однако для них применение армянского алфавита для написания персидского текста имело также моральное и символическое значение.
Keywords: Հայ պարբերական մամուլ; Միջազգային առցանց գիտաժողով